Grüneisen parameter studies on heavy fermion quantum criticality. (6th October 2016) - Gegenwart, Philipp
Abstract: The Grüneisen parameter, experimentally determined from the ratio of thermal expansion to specific heat, quantifies the pressure dependence of characteristic energy scales of matter. It is highly enhanced for Kondo lattice systems, whose properties are strongly dependent on the pressure sensitive antiferromagnetic exchange interaction between f - and conduction electrons. In this review, we focus on the divergence of the Grüneisen parameter and its magnetic analogue, the adiabatic magnetocaloric effect, for heavy-fermion metals near quantum critical points. We compare experimental results with current theoretical models, including the effect of strong geometrical frustration. We also discuss the possibility of using materials with the divergent magnetic Grüneisen parameter for adiabatic demagnetization cooling to very low temperatures.